The political economy of residual state ownership in privatized firms: Evidence from emerging markets - Boubakri, Narjess; Cosset, Jean-Claude; Guedhami, Omrane; Saffar, Walid (Journal of Corporate Finance, 2011)
We investigate the political determinants of residual state ownership for a unique database of 221 privatized firms operating in 27 emerging countries over the 1980 to 2001 period. After controlling for firm-level and other country-level characteristics, we find that the political institutions in place, namely, the political system and political constraints, are important determinants of residual state ownership in newly privatized firms. Unlike previous evidence that political ideology is an important determinant of privatization policies in developed countries, we find that right- or left-oriented governments do not behave differently in developing countries. These results confirm that privatization is politically constrained by dynamics that differ between countries.